Pengaruh Senam Kaki terhadap Neuropati pada Lansia Diabetes Melitus Tipe 2 Puskesmas Colomadu II dan Colomadu I - Prasetiyo, Aridian Regelio; Purwanti, Okti Sri (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Type 2 diabetes mellitus is classified as a chronic metabolic illness that has the potential to produce several complications, with peripheral neuropathy being among the most common. Peripheral neuropathy is characterized by sensory disturbances such as tingling, burning sensation, pain, and numbness in the lower extremities, which, if left untreated, may progress to diabetic foot ulcers and even amputation. One of the non-pharmacological interventions to prevent and reduce neuropathy is foot exercise, which improves blood circulation and enhances peripheral nerve function. To determine the effect of foot exercise on neuropathy levels among elderly patients with type 2 diabetes mellitus at Colomadu II Primary Health Cente: The research adopted a quasi-experimental method with a pretest and posttest control group design. A total of 68 respondents were recruited using purposive sampling, consisting of 34 respondents in the experimental group and 34 in the control group. The intervention was carried out for 3 weeks with a frequency of 3 times per week, lasting ±30 minutes per session. Neuropathy levels were measured using the Toronto Clinical Scoring System (TCSS). Data were analyzed utilizing paired sample t-test and independent sample t-test.The outcomes revealed a significant decrease in neuropathy levels in the experimental group, with the mean score decreasing from 10.56 before the intervention to 7.21 after the intervention (p = 0.001). In contrast, the control group showed no significant changes (p = 0.162). Furthermore, the independent sample t-test revealed a significant difference between the experimental and control groups after the intervention (p = 0.001 < 0.05). Foot exercise has a significant effect in reducing neuropathy levels among elderly patients with type 2 diabetes mellitus. Foot exercise can be recommended as a simple, low-cost, and practical non-pharmacological intervention that patients can perform independently to prevent diabetic neuropathy complications.